ALIRAN GERAKAN FAJAR NUSANTARA (GAFATAR) DALAM PERSPEKTIF MAJELIS ULAMA INDONESIA (MUI) KALIMANTAN BARAT (STUDI KASUS TERHADAP KRONOLOGI LAHIRNYA FATWA MUI KALIMANTAN BARAT TENTANG AJARAN GAFATAR) - Muhammad Rahmatullah (AT-TURATS, 2018)
This writing aims to observe how Indonesian Council of Ulama (MUI) in West Kalimantan responds the appearance of Gafatar sect in West Kalimantan. In fact, the branch of MUI in Indonesia could not deliver the fatwa that Gafatar was misguided sect. Moreover, the MUI of West Kalimantan Province should firstly consult the central MUI in Jakarta before stating the misguided fatwa. Besides, the fatwas of central and regional MUI have generally the similar position and could not abort one another. Should there are some differences, both leaders of MUI (central and regional) could discuss to find the solution.